A Horned Viper Bite Victim with PRES - Ahmed Mustafa Ibrahim; Tarek Talaat ElSefi; Maha Ghanem; Akram Muhammad Fayed; Nesreen Adel Shaban (Case Reports in Neurological Medicine, 2017)
Neurological complications of snake bites have been well documented in the literature as neuromuscular paralysis and cerebrovascular complications; posterior reversible encephalopathy syndrome was rarely described. A 23-year-old lady presented near full term of her pregnancy with a horned snake Cerastes cerastes bite; after successful delivery she started complaining of altered mental status and visual disturbance with ulceration over the site of the snake bite. On admission, the patient had Glasgow Coma Score of 12, blood pressure 130/80 mmHg, temperature 38°C, sinus tachycardia at 120 beats per minute, severe dehydration, and reduction in visual acuity to “hand motion” in both eyes with poor light projection and sluggish pupillary reactions. CT brain was not conclusive; MRI revealed features of PRES. Treatment was mostly supportive within one week; the patient regained consciousness; visual disturbance, however, persisted. This patient as well as the few previously described cases highlights PRES as a possible complication of snake bites.